2004
DOI: 10.1248/bpb.27.1527
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Induces a Caspase-Independent But Mitochondria- and MAPK-Dependent Cell Death in the Murine Fibrosarcoma Cell Line L929

Abstract: Oridonin, a diterpenoid isolated from Rabdosia rubescens, has various pharmacological and physiological effects such as anti-inflammation, anti-bacteria, anti-tumor effects [1][2][3] and has been used for the treatment of human cancers, especially esophageal carcinoma. 4) Our previous study showed that oridonin had cytotoxic effects on four tumor cell types, human melanoma A375-S2, human cervical carcinoma HeLa, human breast adenocarcinoma MCF-7, and murine fibrosarcoma L929.5) However, the mechnasim of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
44
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“…32,33 Previous study showed that oridonin could enhance L929 cell death by activating ERK-dependent MAPK pathway. 34 In this study, we demonstrated that EriB addition to Kasumi-1 cells resulted in an inhibition of ERK1/2 phosphorylation and activation of AP-1, providing evidence that EriB could interfere with ERK1/2 . This could represent one of the NF-kB-independent mechanisms in EriB-induced apoptosis.…”
Section: Discussionsupporting
confidence: 51%
“…32,33 Previous study showed that oridonin could enhance L929 cell death by activating ERK-dependent MAPK pathway. 34 In this study, we demonstrated that EriB addition to Kasumi-1 cells resulted in an inhibition of ERK1/2 phosphorylation and activation of AP-1, providing evidence that EriB could interfere with ERK1/2 . This could represent one of the NF-kB-independent mechanisms in EriB-induced apoptosis.…”
Section: Discussionsupporting
confidence: 51%
“…Recently, other investigators showed that oridonin induced apoptosis in association with up-regulation of proapoptotic protein Bax in murine fibrosarcoma L929 cells (25). In the present study, oridonin slightly increased levels of Bax in MT-1 cells, but not in MT-2 and RPMI8226 cells.…”
Section: Discussionsupporting
confidence: 46%
“…46 There are very limited studies on the regulation and function of MAPKs in oridonin-induced cell death. Oridonin has been demonstrated to induce the activation of ERK1/2 and inactivation of p38 MAPK in human macrophage-like U937 cells, murine fibrosarcoma cell line L929 and A375-S2 cell line 9,22,47,48 whereas, the activities of JNK was not affected by oridonin. 47 Inconsistent with these reports, our study demonstrated that oridonin treatment induced marked inactivation of ERK and activation of p38 MAPK and JNK.…”
Section: Discussionmentioning
confidence: 97%